2007
DOI: 10.1177/1086026607305739
|View full text |Cite
|
Sign up to set email alerts
|

Place Attachment and Environmental Change in Coastal Louisiana

Abstract: This article examines how residents of communities frame environmental change. Specifically, how do respondents from Louisiana's coastal communities understand coastal wetland loss? For this article, the authors rely on 47 in-depth interviews from communities in two coastal parishes (counties). Respondents convey the meanings they give to land loss through constructing a narrative of place. The authors use a phenomenological approach that focuses on how stories are told and the subjective interpretations of so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
96
0
3

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(101 citation statements)
references
References 21 publications
2
96
0
3
Order By: Relevance
“…Environmental psychologists and sociologists have developed several concepts-sense of place, place meaning, place attachment-to study people's relationship with place, and have demonstrated its role in place-related attitudes and behaviors (Burley et al 2007, Lewicka 2011a, Willox et al 2012, however there is an underrepresentation of sense of place in adaptation planning and decisions (Agyeman et al 2009, Adger et al 2011. Social-ecological systems (SES) literature has started to engage with place theory to better understand how people register, experience, and manage SES change (Chapin and Knapp 2015, Stedman 2016, Masterson et al 2017.…”
Section: Introductionmentioning
confidence: 99%
“…Environmental psychologists and sociologists have developed several concepts-sense of place, place meaning, place attachment-to study people's relationship with place, and have demonstrated its role in place-related attitudes and behaviors (Burley et al 2007, Lewicka 2011a, Willox et al 2012, however there is an underrepresentation of sense of place in adaptation planning and decisions (Agyeman et al 2009, Adger et al 2011. Social-ecological systems (SES) literature has started to engage with place theory to better understand how people register, experience, and manage SES change (Chapin and Knapp 2015, Stedman 2016, Masterson et al 2017.…”
Section: Introductionmentioning
confidence: 99%
“…Results indicate that the concept is potentially important in explaining pro-environmental behaviours across a range of settings and contexts. It appears that such behaviours are more likely to result when the individual is positively attached to a place (Burley, Jenkins, Laska, & Davis, 2007;Walker & Ryan, 2008). Walker and Chapman (2003) suggest that knowledge about a place increases the likelihood of place-protective behaviours among individuals and can generate a sense of commitment and responsibility vis-à-vis places they are most attached to (Relph, 1976).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, others, as elaborated earlier, are contemplating leaving MRV, and juggle the trade-offs between staying in a place they are attached to and being better off somewhere else (Coulthart 2012). While individual responses differ, villagers' particular ways of life, history, and culture are closely associated with the physicality of MRV (Burley et al 2007). Hence, the loss of the physical site has the potential to result in larger lifestyle losses (as discussed by Turner et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…In a coastal context, research has shown that physical alteration and loss of coast often affect localized conceptions of identity and belonging (O'Collins 1990, Burley et al 2007, Graham et al 2014. A recent study from Korsra, Micronesia (Monnereau and Abraham 2013) illustrates that coastal erosion can have a series of adverse consequences at the local level.…”
Section: Introductionmentioning
confidence: 99%